Membangun Personal Branding melalui YouTube - Widya Nur Bhakti Pertiwi; Arum Wahyuni Purbohastuti; Enok Nurhayati (LUGAS Jurnal Komunikasi, 2020)
This research generally aims to develop personal branding research with social media. The previous research took Instagram, Facebook, or Twitter media, but this research focuses on personal branding on YouTube. This research method is a qualitative and descriptive method by observing Raditya Dika YouTube Channel and interviews with several Subribers Raditya Dika. The study describes the situations or events and does not seek links, hypotheses, or make predictions. In this research, the indicators of personal branding are authenticity,  integrity, consistency, specialization, authority, distinctiveness, relevance, visibility, persistence, goodwill, and performance. The subject of this research is Raditya Dika's YouTube channel, and the object of this research is a personal brand Raditya Dika through a personal YouTube channel. The results show that Raditya Dika can form, even enhance a positive image by establishing personal branding through YouTube.